A mobile phone-based intervention to improve health screening uptake: a randomized experiment in Indonesia - Marcus, Maja E.; Reuter, Anna; Rogge, Lisa; Vollmer, Sebastian (American Economic Association, 2019)
Our study measures the impact of informative text messages on the uptake of screening for non-communicable diseases (NCDs) such as hypertension and diabetes. The text messages contain information on free public screening services as well as facts about hypertension and diabetes. We test the effect of these messages against no treatment. Our main outcome is the self-reported usage of screening services in the past months, measured at the endline.